The Evolution of Methotrexate Applications: A Multidimensional Approach to Treating Various Disorders – A Literature Review - Tamborski, Tomasz; Zagalska, Michalina; Ząbek, Adam Jan; Kuźniar, Jakub Paweł; Turek , Marta; Grzebinoga , Adam; Szlążek , Julia; Roguska, Barbara; Szostak, Magdalena; Chrzanowska , Emilia Gabriela (Journal of Education, Health and Sport, 2025)
Introduction Methotrexate (MTX) is a key cytostatic and immunosuppressive drug widely used in oncology and autoimmune disease treatment. It acts as a folic acid antagonist, inhibiting DNA synthesis and cell division. This review explores new applications of MTX beyond its traditional role. MTX shows potential in treating neuromyelitis optica spectrum disorders (NMOSD) as an alternative when other immunosuppressants are ineffective. In ophthalmic diseases like non-infectious uveitis and scleritis, it reduces inflammation and corticosteroid dependence. MTX is also used for unruptured ectopic pregnancy as a non-surgical option in select cases, with meta-analyses confirming its effectiveness, though resolution times may vary. Additionally, emerging evidence suggests MTX may help prevent cardiovascular diseases in patients with inflammatory conditions by improving atherosclerosis biomarkers. Objective This review aims to provide an overview of MTX’s expanding applications, pharmacological properties, and the importance of therapy monitoring. Current State of Knowledge MTX is well-established in both low doses for autoimmune diseases like rheumatoid arthritis and high doses for chemotherapy. While effective, it has significant toxicity risks, particularly at high doses, necessitating therapeutic drug monitoring (TDM) to minimize adverse effects like nephrotoxicity and mucositis. Methods This review synthesizes data from review articles, original studies, meta-analyses, and clinical guidelines, covering MTX’s mechanisms, pharmacokinetics, clinical applications, toxicity management, and TDM role. Conclusions MTX remains a cornerstone in disease treatment due to its broad pharmacological spectrum. Effective therapy requires proper dosing, toxicity management, and monitoring strategies. Ongoing research seeks to optimize MTX use while minimizing risks.